Taylor series expansion with the fluctuation freely approximated remainder over highly oscillatory basis functions - (:unkn) unknown (My University, 2009)
A new formulation is devefoped here to approximate highly oscillatory functions by applying the Fluctuationlessness Theorem to the remainder term of the Taylor polynomial. To this end a trigonometric basis set is utilized. Because of the limitation of space in this extended abstract the implementation of results are left to the presentation. 2009 American Institute of Physics.
Keywords: Approximation Methods; Fluctuation Expansion; Oscillatory Functions; Taylor Polynomials; Trigonometric Basis Set